Innovations in Additive Manufacturing for Socket Fabrication: An Overview - Faiza, Linda Ziyadatul; Caesarendra, Wahyu; Lestari, Wahyu Dwi (Universitas Negeri Malang, 2024)
Additive Manufacturing (AM) has transformed the prosthetics industry, particularly in socket production, which plays a critical role in the comfort, fit, and functionality of prosthetic limbs. This article examines the latest advancements in AM technologies and their applications in socket fabrication. Key techniques like stereolithography (SLA), selective laser sintering (SLS), and fused deposition modeling (FDM) have facilitated the production of highly personalized, lightweight, and durable prosthetic sockets. These methods not only improve design precision but also allow for the use of biocompatible, flexible materials, enhancing both comfort and functionality. Digital design tools have streamlined the production process, reducing lead times and costs, while improving accuracy and repeatability in socket manufacturing. This review explores the current state of AM in prosthetic socket development, emphasizing the benefits, challenges, and future directions of this fast-evolving field. By analyzing recent research and case studies, the article provides insights into how AM is reshaping prosthetics, offering more accessible solutions for individuals needing prosthetic limbs. It also discusses the challenges of material selection, regulatory considerations, and the potential for scaling production for broader use.